Special zone in multi-layer and multi-pass welded metal and its role in the creep behavior of 9Cr1Mo welded joint. (15th October 2016) - Liu, Wen; Lu, Fenggui; Wei, Yuanhang; Ding, Yuming; Wang, Peng; Tang, Xinhua
Abstract: The creep properties of 9Cr1Mo welded joint are determined by special zone (SZ) in equiaxed grain zone of welded metal (WM) suffered from multiple thermal cycles during multi-layer and multi-pass welding process. The SZ in WM was characterized in detail and its role in creep behavior was discussed in this paper. The creep test of 9Cr1Mo welded joint was carried out in 566 °C under 270 MPa and 250 MPa, and great difference of fracture morphology was observed as "cup and cone" and "wave" shapes, respectively. The cup and cone fracture consists of many deep and cone-shaped dimples. For wave-shaped fracture, some honeycomb-like structure is observed at bottom and top of wave, which is shallow and inclined to coalesce. Banded structure along prior austenite grain boundaries inside SZ is responsible for wave fracture. Some small grains with size of about 2 μm are observed in banded structure, which increases the real length of the grain boundary and might deteriorate the creep performance. For long-term creep behavior, creep voids and cracks firstly form along boundaries of small grains in banded structure of SZ, and then creep crack propagates along the fusion line direction of weld beads. Grain boundary failure induced by banded structure is considered as the main rupture mechanism in this condition. Graphical abstract: Highlights: Creep fracture occurs in the middle of the WM during creep tests at 566 °C. SZ in multi-layer and multi-pass WM could determine creep fracture mechanism. Crater and wave shape fracture were observed under 270 MPa and 250 MPa, respectively. Banded structure along PAGBs inside SZ is responsible for wave fracture. Grain boundary failure induced by banded structure is the main creep rupture mechanism.